Study of Chemical Composition and Physical Characteristics of Pellets Based on Roughage Feedstuff - Hidayah, Kharisma Taufiqa; Sari, Putri Candrika; Noviandi, Cuk Tri; Agus, Ali; Astuti, Andriyani; Anam, Moh Sofi'ul; Paradhipta, Dimas Hand Vidya (Faculty of Animal Science, Universitas Brawijaya, 2025)
The pellets were produced from peanut straw (PTS), water spinach (WSP), Leucaena leucocephala leaves (LLL), Gliricidia sepium leaves (GSL), and Calliandra calothyrsus leaves (CCL). Each feedstuff was pelletized with the addition of 8% tapioca flour as a binder. The pellets were tested for chemical characteristics, physical appearance, and physical characteristics, which included the pellet length, density, stacking density, stacking compaction density, modulus of uniformity, modulus of fineness, pellet durability index (PDI), and water absorption. The data were analysed descriptively. The results of this research revealed that the nutritional composition of the pellets followed that of the raw feedstuff. All the pellets varied in color depending on the color of the raw material and had a medium texture. Each pellet had specific physical characteristics. The colors of PTS, LLL, GSL, and CCL were dark green, whereas WSP was dark brown. All single pellets had a medium texture, with PDI values above 97% and MF values greater than 4.1, which classified them into the coarse group. In terms of water absorption, the CCL had the longest absorption time, approximately 75.17 minutes, whereas the other pellets had absorption times less than 30 minutes. As a result, although a single feed ingredient can be produced as pellets, the physical and chemical qualities depend on the origin of the ingredient.